2020
DOI: 10.1111/jce.14349
|View full text |Cite
|
Sign up to set email alerts
|

Five‐year outcomes after catheter ablation for atrial fibrillation in patients with hypertrophic cardiomyopathy

Abstract: Background Catheter ablation (CA) is a promising option in most patients with refractory atrial fibrillation (AF). However, data on over 5 years' outcomes with larger numbers in hypertrophic cardiomyopathy (HCM) patients with AF have not been reported. We assessed the outcome of 120 HCM patients following CA compared with a non‐CA group and general patients without AF matched by HCM type with a 61.9 ± 31.6‐month follow‐up. Methods and Results A total of 120 patients (age 61 ± 9.8 years, female n = 43, 35.8%) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 21 publications
1
13
0
Order By: Relevance
“…Limitations include its retrospective nature, lack of a uniform ablation protocol, and inclusion of cases performed early in the field's history. Their results are broadly comparable to those obtained with other large cohorts and meta‐analyses 6,7 . Overall, the study supports the 2020 AHA/ACC HCM guideline's IIa B‐NR recommendation that “catheter ablation for AF can be effective when drug therapy is ineffective, contraindicated, or not the patient's preference.” 8 …”
supporting
confidence: 84%
“…Limitations include its retrospective nature, lack of a uniform ablation protocol, and inclusion of cases performed early in the field's history. Their results are broadly comparable to those obtained with other large cohorts and meta‐analyses 6,7 . Overall, the study supports the 2020 AHA/ACC HCM guideline's IIa B‐NR recommendation that “catheter ablation for AF can be effective when drug therapy is ineffective, contraindicated, or not the patient's preference.” 8 …”
supporting
confidence: 84%
“…Recent advances in technology though have resulted in more durable lesions with better procedural and follow-up results 19 . Together with emerging modifying drug therapies like Mavacamten 8 10 , these findings argue for early intervention before advanced atrial remodeling takes place 20 , 21 .…”
Section: Discussionmentioning
confidence: 93%
“…The fibrotic process possibly plays a crucial role in the development and maintenance of AF. 8,9 Keeping in mind that only young patients with paroxysmal AF and less dilated atria display better long-term outcomes, [3][4][5] the presence of LA cardiomyopathy with respect to the progression of the disease might have important implications in ablation outcomes. HCM patients undergo catheter ablation late in the course of their disease (median of 5.9 years after the diagnosis of atrial arrhythmias), 3 and therefore an extensive structural and electrical remodeling including LA enlargement and fibrosis is possibly present at the time of catheter ablation.…”
Section: Discussionmentioning
confidence: 99%
“…2 Studies addressing the efficacy of AF CA in patients with HCM are limited and have demonstrated worst long-term outcomes compared to non-HCM patients. [3][4][5][6][7] Persistent AF, female gender, age, New York Heart Association (NYHA) functional class, LA enlargement, and left ventricle (LV) outflow tract obstruction have been proposed as predictors of AF recurrence following catheter ablation in this specific population. [3][4][5] Pulmonary vein (PV) isolation only appears insufficient to improve the long-term arrhythmia survival in HCM patients, possibly due to extensive LA remodeling.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation